INVENTORY CONTROL MODEL WITH APPLICATIONS USING THE MICROSOFT VISUAL BASIC 6.0 - Hindro Hindrianto; Drs. Sunarto Usna, MMSI (Jurnal Sistem Informasi, 2003)
The use of mathematical models of inventory control is very useful for the management of a company producing or trading in saving time and cost when compared with the usual planning or management. The process of finding important variables in the model such as the total purchases of Inventory Control is optimal, the optimal time of purchase and reorder point calculations yield a more rapid, accurate and easy compared with manual calculation.Accuracy of the calculations to help the success in managing and controlling inventories, and ultimately, the proper inventory control will save the company budget.